Laboratory Model Test Research on Mechanical Characteristics of Anchor in Loess Tunnel under the Action of Pull-Out Load - Zhongming Su; Jianxun Chen; Yanbin Luo; Xin He (Advances in Civil Engineering)
The deformation mode of loess surrounding rock of anchor under the action of pull-out load and the shear stress distribution law of loess anchor and loess interface under the condition of different lengths anchor are studied by using the laboratory self-made model test chamber and micro anchor pullout instrument. A total of three tests are carried out for the selected test anchor. Three deformation modes of loess surrounding rock under the action of pull-out load are obtained according to the test results. It is proposed that the maximum shear stress of loess anchor under the action of pull-out load appears in the section 25 times the anchor diameter from the anchor head, and the shear stress in the middle and rear part of the anchor body can only be brought into full play when the length-to-diameter ratio of the anchor body is 110 or more. Based on the displacement solution of Mindlin problem, the drawn conclusion is compared with the theoretical solution of shear stress and axial force of loess anchor under the action of pull-out load. The results compared are basically consistent, indicating that the conclusion has strong engineering practice, which can provide technical basis for the design and optimization of the system anchor in the sidewall of loess tunnel.